Case of salvage en bloc vertebrectomy for locally progressive T12 breast cancer metastasis after failed radiotherapy and systemic therapy - Isamu Miura; Takayoshi Shimizu; Takahiro Hori; Hanako Morisawa; Suguru Nakamura; Kaname Ito; Naohisa Miura; Kotaro Kohara (Surgical Neurology International, 2026)
Background: Isolated local progression of breast cancer spinal metastases may occur despite adjunctive radiotherapy and systemic therapy. Here, a 71-year-old female underwent a salvage en bloc vertebrectomy for a locally progressive T12 breast cancer spinal metastasis that newly developed due to failure of prior adjunctive radiotherapy and systemic therapy. Case Description: A 71-year-old female developed a T12 spinal metastasis 10 years after surgery for breast cancer; she exhibited no other metastatic lesions. Despite endocrine therapy, chemotherapy, targeted therapy, and radiotherapy, the lesion progressed, resulting in severe spinal stenosis, severe back pain, and paraparesis. Salvage en bloc T12 vertebrectomy was performed; this required piecemeal removal of the involved posterior elements. Postoperatively, the patient’s severe pain resolved, ambulation was restored, and no local recurrence was later documented for 6 months. Conclusion: Salvage en bloc vertebrectomy may be a valuable treatment option for carefully selected patients with isolated locally progressive breast cancer spinal metastasis after failure of radiotherapy and systemic therapy.